Vaccine refusal/ hesitancy- the ethical standpoint regarding the COVID-19 pandemic - João Daniel da Cruz Gentil (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To reflect about vaccine hesitancy from ethical and bioethical perspectives. Methodology: Reflective study through the analysis of bibliographic research carried out from December 2020 to May 2021 in the data banks SciELO, PubMed, Direção Geral da Saúde, and Ordem dos Enfermeiros. Results: Vaccination aims at collective protection. The effects desirable in the individual do not have the same ethical value in the collective, leading to cost-benefit imbalances. The insufficiency of principlist Bioethics leads us to use other moral values, such as responsibility, solidarity, and social justice, to reflect on problems related to vaccination. Conclusion: In ethics there are no perfect solutions, and they depend on the context. Group immunity is one of the most discussed issues in a pandemic. Equitable distribution and the principle of justice are reflected daily in the nursing profession.